Congenital hypotrichosis and partial anodontia in a crossbred beef calf - Barlund, Christy S. (Canadian Veterinary Medical Association, 2007)
Clinical examination, skin biopsies, skull radiographs, and DNA analysis of a 2-day-old Red Angus-Charolais-Simmental cross bull calf confirmed the diagnosis of congenital hypotrichosis and anodontia defect (HAD), also called anhidrotic ectodermal dysplasia, which is a rare anomaly caused by a deletion in the bovine EDA gene on the X chromosome.